2021
DOI: 10.1002/andp.202100296
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Behind Entanglement: A Spectral Approach to the Quantum Internet

Abstract: In this study, the bridge between quantum fourier transform (QFT) and the most important effect inside quantum physics-entanglement-is presented. Moreover, all the applications of entanglement are impregnated by this equivalence, which concludes in the first spectral approach to the quantum Internet of the literature, which will allow the development of configurations that are more immune to noise as well as fault-tolerant. Several protocols used in the quantum Internet are implemented on a 5-qubit internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Moreover, between the preliminary works mentioned above [3][4][5][6] and the present study we will verify that the en- tanglement is organized in layers of QFT blocks and that a first layer (like the first cut of a distillation column) gives us a rustic version of entanglement, while a second layer (that is, through a complete distillation) gives us a maximally entangled version [1,[35][36][37] of the particles resulting from this process.…”
Section: Contribution and Reachsupporting
confidence: 75%
See 4 more Smart Citations
“…Moreover, between the preliminary works mentioned above [3][4][5][6] and the present study we will verify that the en- tanglement is organized in layers of QFT blocks and that a first layer (like the first cut of a distillation column) gives us a rustic version of entanglement, while a second layer (that is, through a complete distillation) gives us a maximally entangled version [1,[35][36][37] of the particles resulting from this process.…”
Section: Contribution and Reachsupporting
confidence: 75%
“…In previous works, [3][4][5][6] it was shown that quantum entanglement requires the intervention of two QFT blocks in its constitution. In this study, it is shown that the intervention of a single QFT block gives rise to a new type of entanglement with characteristics markedly differentiated from those present in its traditional forms, i.e., those manifested in the maximally entangled states, [1,47,48] and in the called nonmaximally entangled states.…”
Section: Contribution and Reachmentioning
confidence: 99%
See 3 more Smart Citations